Impact of Hedonistic Lifestyle to the Impulsive Buying of Students through the Perspective of Islamic Economy - Atika, Atika Rizki; Wahab, Abdul; Bin Sapa, Nasrullah (LAA MAISYIR : Jurnal Ekonomi Islam, 2023)
The groups most vulnerable to this lifestyle are teenagers or students. The focus of this research is hedonic lifestyle on students’ impulsive behavior from an Islamic economic perspective. This research approach is qualitative and is a phenomenological type of research, collecting through interviews, observation. The research results show that the hedonic lifestyle of FEBI UIN Alauddin Makassar students has a significant impact on consumer behavior and encourages impulsive purchases. This is contrary to Islamic values ​​which condemn waste. This research provides knowledge about the factors that influence hedonic lifestyles and impulsive behavior in students, and emphasizes the conflict between this behavior and Islamic economic principles. The conclusion of this research is the need for in-depth understanding, awareness and self-control of hedonic lifestyles among students in order to minimize impulsive consumption behavior which is contrary to Islamic economic values.